Crosstalk between Depression, Anxiety, and Dementia: Comorbidity in Behavioral Neurology and Neuropsychiatry - Tanaka, Masaru (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This Special Issue highlights the most recent research on depression, anxiety and dementia, with attention to comorbidity in a range of diseases. The symptoms of depression, anxiety and dementia are the most common comorbid manifestations present in patients suffering from neurodegenerative and psychiatric diseases. Together, these illnesses constitute an extremely complex and challenging research field due to their inherent multifactorial causative factors, heterogeneous pathogenesis, and mental and behavioral manifestations. This Special Issue covers laboratory, clinical and statistical studies on the crosstalk between depression, anxiety, dementia, Alzheimer's disease, multiple sclerosis, schizophrenia, diabetes mellitus, Down's syndrome, and/or compulsive disorders. It contains contributions from 71 authors, has been reviewed by 25 referees, and edited by three academic editors and one managing editor.